INTERNAL ENVIRONMENTAL POLLUTION PERSPECTIVE HADITH - Fattah, Abdul; Asse, Ambo; Gassing, A Qadir; Zulfahmi, Zulfahmi (Program Pascasarjana, UIN Alauddin Makassar, 2021)
Environmental pollution in the perspective of the Prophet's hadith. what is meant here is a study of the hadith of the Prophet. which discusses environmental pollution with 3 issues that will be discussed 1) how is the quality of the hadith about environmental pollution, 2) how is the content of the hadith about environmental pollution both formally and substantially, and 3) what are the implications of the meaning of the hadith about environmental pollution and efforts prevention. The type of research used is descriptive with a rationalistic style, namely describing the quality, validity, and analysis of the traditions of the Prophet Muhammad, both in the aspect of the sanad and its matan. This research includes source studies (text review) because the emphasis is more on library research. In the research library, data is collected by quoting, adapting, and analyzing using content analysis on representative literature that has relevance to the problems discussed, then reviews and concludes. The results of research on environmental pollution in the perspective of the Prophet's hadith; First, the hadith of the Prophet (saw) related to environmental pollution has authentic quality. Second, a) the essence of environmental pollution is the occurrence of changes in a substance (water, soil or air) due to the inclusion of other components in it that can affect the quality of the environment (water, soil or air). b) forms of environmental pollution and their impacts include 1) prohibition of urination in stagnant water as a form of environmental pollution of water, 2) prohibition of defecating in public places, and water sources as a form of soil and water pollution, 3) prohibition of elevating buildings that block surrounding housing from clean air and prohibition of directing dirty air to it as a form of air pollution. Third, solutions to environmental pollution, namely; 1) Go green 2) Go clean, and 3) Environmental conservation. Based on the results of the study, it is recommended that UIN Alauddin Makassar establish a Center for Environmental Studies in order to give birth to Environmental Fiqh (fiqh of land, water and air) and that Government agencies engaged in the field of Environment in an effort to overcome environmental pollution to strengthen existing regulations even need to made new regulations in an effort to preserve the environment with a religious science approach. 3) prohibition of elevating buildings that block surrounding housing from clean air and prohibition of directing dirty air to it as a form of air pollution. Third, solutions to environmental pollution, namely; 1) Go green 2) Go clean, and 3) Environmental conservation. Based on the results of the study, it is recommended that UIN Alauddin Makassar form a Center for Environmental Studies in order to give birth to Environmental Fiqh (fiqh of land, water and air) and that Government agencies engaged in the field of Environment in an effort to overcome environmental pollution to strengthen existing regulations even need to made new regulations in an effort to preserve the environment with a religious science approach. 3) prohibition of elevating buildings that block surrounding housing from clean air and prohibition of directing dirty air to it as a form of air pollution. Third, solutions to environmental pollution, namely; 1) Go green 2) Go clean, and 3) Environmental conservation. Based on the results of the study, it is recommended that UIN Alauddin Makassar form a Center for Environmental Studies in order to give birth to Environmental Fiqh (fiqh of land, water and air) and that Government agencies engaged in the field of Environment in an effort to overcome environmental pollution to strengthen existing regulations even need to made new regulations in an effort to preserve the environment with a religious science approach. 1) Go green 2) Go clean, and 3) Environmental conservation. Based on the results of the study, it is recommended that UIN Alauddin Makassar form a Center for Environmental Studies in order to give birth to Environmental Fiqh (fiqh of land, water and air) and that Government agencies engaged in the field of Environment in an effort to overcome environmental pollution to strengthen existing regulations even need to made new regulations in an effort to preserve the environment with a religious science approach. 1) Go green 2) Go clean, and 3) Environmental conservation. Based on the results of the study, it is recommended that UIN Alauddin Makassar form a Center for Environmental Studies in order to give birth to Environmental Fiqh (fiqh of land, water and air) and that Government agencies engaged in the field of Environment in an effort to overcome environmental pollution to strengthen existing regulations even need to made new regulations in an effort to preserve the environment with a religious science approach.